2012
DOI: 10.1111/j.1365-2486.2012.02752.x
|View full text |Cite
|
Sign up to set email alerts
|

How do temperate bryophytes face the challenge of a changing environment? Lessons from the past and predictions for the future

Abstract: Bryophytes are a group of early land plants, whose specific ecophysiological and biological features, including poikilohydry, sensitivity to moderately high temperature and high dispersal ability, make them ideal candidates for investigating the impact of climate changes. Employing a combined approach of species distribution modelling (SDM) and molecular phylogeography in the temperate moss Homalothecium sericeum, we explore the significance of the Mediterranean refugia, contrasting the southern and northern r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 74 publications
5
34
0
Order By: Relevance
“…The presence of such hyper-oceanic species as Saccogyna viticulosa and Dicranum scottianum in western Scandinavia and western Iberian Peninsula should hence be considered as an irradiation of an Atlantic element into regions that otherwise belong to the core Alpine and Mediterranean regions, respectively. This spatial congruence found between biogeographic regions defined for vascular plants and bryophytes reinforces the notion that, despite the substantial differences in ecophysiology and dispersal ability between the two groups, post-glacial migration patterns might have been much more similar between them than previously thought [68].…”
Section: Discussionsupporting
confidence: 77%
“…The presence of such hyper-oceanic species as Saccogyna viticulosa and Dicranum scottianum in western Scandinavia and western Iberian Peninsula should hence be considered as an irradiation of an Atlantic element into regions that otherwise belong to the core Alpine and Mediterranean regions, respectively. This spatial congruence found between biogeographic regions defined for vascular plants and bryophytes reinforces the notion that, despite the substantial differences in ecophysiology and dispersal ability between the two groups, post-glacial migration patterns might have been much more similar between them than previously thought [68].…”
Section: Discussionsupporting
confidence: 77%
“…Employing a combined approach of SDMs and molecular phytogeography, the significance of the Mediterranean refugia, contrasting the southern and northern refugia hypotheses, has been highlighted for some mosses such as the temperate species Homalothecium sericeum (Désamoré et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…long before the LGM). Désamoré et al (2012) found northern refugia the most likely origin of the northern European colonization. Haplotype groups restricted to southwestern genetic clusters are also found in Kindbergia praelonga (Hedw.)…”
Section: The Southern Elementmentioning
confidence: 99%